Atresia de vias biliares em paciente com síndrome do olho do gato - relato de caso - Bruna Caseri Marino; Sabrina Sayuri Suzuki; Lucas Rocha Alvarenga; Gabriel Hessel; Antonio Fernando Ribeiro; Elizete Aparecida Lomazi; Adriana Maria Alves de Tommaso; Roberta Vacari de Alcântara; Maria Angela Bellomo Brandão (Sociedade Brasileira de Pediatria, 2023)
Biliary atresia is a rare condition, of undefined etiology and with a potentially fatal evolution. The cat eye syndrome is a rare chromosomal disease that is associated with several malformations, biliary atresia being among the most rarely described. Male newborn with jaundice onset at 20 days of age, accompanied by fecal hypocholia. Laboratory tests, imaging and liver biopsy were suggestive of biliary atresia. The patient underwent Kasai surgery at 55 days of age. He also had several malformations, and the genetic team diagnosed cat eye syndrome. He presented with a favorable clinical evolution after surgery, maintaining follow-up with several specialties. This genetic syndrome has a variable phenotype and the early identification of associated malformations is essential for proper treatment, which can have a positive impact on both patient survival and quality of life.